District plans in reindeer husbandry in Northern Norway. Roles and challenges - Eira, Biret-Risten (UiT Norges arktiske universitet, 2017)
This thesis deals with the reindeer husbandry’s district plans, and are industry’s own official document. They provide information about the reindeer husbandry practiced in the reindeer grazing district. The plans should provide information necessary for the public planning and should function as a tool to reduce conflicts and enhance cooperation among reindeer herders and other users. I have examined the reasons why the district plans have not functioned as intended by looking at the experiences and expectations with the plans. Methods used are depth-interviews, document analysis and participating in meetings. The plans have not so far prevented conflicts, nor enhanced the cooperation and communication between the reindeer herders and the municipalities because of the lack of awareness of the plans. In addition to unawareness about the plans, I argue that the challenges related to the plans can be explained by insufficient knowledge about reindeer husbandry and different “glances” on the tension between flexibility and rigidity. In particular, the issue of classification of land illustrate this tension.